Patient-reported Outcomes at 6 to 12 Months Among Survivors of Firearm Injury in the United States. Issue 6 (December 2021) - Herrera-Escobar, Juan Pablo; de Jager, Elzerie; McCarty, Justin Conrad; Lipsitz, Stuart; Haider, Adil H.; Salim, Ali; Nehra, Deepika
Abstract : Objective: Assess outcomes in survivors of firearm injuries after 6 to 12 months and compared them with a similarly injured trauma population. Background: For every individual in the United States who died of a firearm injury in 2017, three survived, living with the burden of their injury. Current firearm research largely focuses on mortality and short-term health outcomes, while neglecting the long-term consequences. Methods: We contacted adult patients with a moderate-to-severe injury from a firearm or motor vehicle crash (MVC) treated at 3 level I trauma centers in Boston between 2015 and 2018. Patients were contacted 6 to 12 months postinjury to measure: presence of daily pain; screening for post-traumatic stress disorder (PTSD); new functional limitations; return to work; and physical and mental health-related quality of life. We matched each firearm injury patient to MVC patients using Coarsened Exact Matching. Adjusted Generalized Linear Models were used to compare matched patients. Results: Of 177 eligible firearm injury survivors, 100 were successfully contacted and 63 completed the study. Among them, 67.7% reported daily pain, 53.2% screened positive for PTSD, 38.7% reported a new functional limitation in an activity of daily living, and 59.1% have not returned to work. Compared with population norms, overall physical and mental health-related quality of life was significantly reduced among firearm injury survivors. Compared with matched MVC survivors (n = 255), firearm injury survivors were significantly more likely to have daily pain [adjusted odds ratio (OR) 2.30, 95% confidence interval (CI) 1.08–4.87], to screen positive for PTSD (adjusted OR 3.06, 95% CI 1.42–6.58), and had significantly worse physical and mental health-related quality of life. Conclusions: This study highlights the need for targeted long-term follow-up care, physical rehabilitation, mental health screening, and interventions for survivors of firearm violence.